The Statement of Health and Children Growth Behind Javanese Local Wisdoms - Firngadi, Moetrarsi SK (Open Access Indonesia Journal of Social Sciences, 2020)
Local wisdom emerges through internal processes and lasts a long time as a result of interactions between humans and their environment. This long evolutionary process will lead to the emergence of a crystallized value systemin the form of common law, beliefs and local culture. Thus, in essence local wisdom is a norm that is adhered to in society which is believed in faith and becomes a reference in everyday life. Local wisdom is the positive behavior of humans in interacting with nature and the local environment which comes from the values of religious customs, ancestral advice or local culture, which are naturally built in a society to adapt to their local environment. This literature review aims to raise local wisdom in the form of traditions in Javanese society, especially those related to health and care for children.